Customising learning programmes to the organisation and its employees: how HRD practitioners create tailored learning programmes. (27th May 2005) - Poell, Rob F.; Van Der Krogt, Ferd J.
This study investigates how HRD practitioners customise learning programmes, that is, tailor them to take into account the demands set by organisation and participants. A theoretical account of the relations between learning programmes and organisational/individual characteristics is provided. Results from an action-research project involving 13 learning programmes conducted in healthcare institutions are presented. The main conclusion of the study is that the seven HRD practitioners in our sample used few strategies to customise learning programmes.